Evidenced-based approach to the design and redevelopment of inclusive technology enhanced learning environments : final report. - Wood, Denise; Scutter, Sheila; Viljoen, Renette (Australia, Dept of Education and Training, 2017)
Final report from a project involving academics from four Australian and three international universities, Indigenous communities, the not-for profit sector and open-source community. The project aimed to demonstrate the benefits of an evidence-based approach to the design of inclusive technology enhanced learning (TEL) environments; provide guidelines on the design and redevelopment of inclusive online curricula; and develop a prototype of an open source responsive learning system, which adapts to student needs by delivering content that is personalised to meet their accessibility needs and learning preferences. The project addressed several priority areas of the Innovation and Development Grants program, with the major foci being innovative use of technology, curriculum design, and strategic approaches to student success, progression and diversity. The project involved development of a framework and guidelines, as well as case studies of best practice to guide academics in the design of TEL approaches that facilitate learner engagement within an inclusive, personalised learning environment.